2011
DOI: 10.5489/cuaj.10159
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lymphatic pathway involved in the spreading of prostate cancer by fluorescence navigation approach with intraoperatively injected indocyanine green

Abstract: Objective: The objective of this study was to identify lymphatic vessels draining from the prostate by using a fluorescence navigation (FN) system. Methods: Fourteen subjects were candidates for radical retropubic prostatectomy (RRP) and pelvic lymph node dissection (PLND). After an indocyanine green solution was injected into the prostate during RRP, lymphatic vessels draining from the prostate were analyzed using a FN system. After PLND based on lymphatic mapping by the FN system (in vivo probing) was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 13 publications
1
27
0
4
Order By: Relevance
“…The clinical superiority of the FN system to the RI-assisted one is due to the ease of tracking the lymphatic vessels into the pelvic LNs under FN guidance. 9 The results we obtained showed that the intensity of ICG fluorescence either in vivo or ex vivo was the strongest in the internal iliac region, second strongest in the obturator region, and weakest in the external iliac region. These results indicate that the major lymphatic channels involved in the spread of bladder cancer are those along the inferior vesical artery to the internal iliac artery.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The clinical superiority of the FN system to the RI-assisted one is due to the ease of tracking the lymphatic vessels into the pelvic LNs under FN guidance. 9 The results we obtained showed that the intensity of ICG fluorescence either in vivo or ex vivo was the strongest in the internal iliac region, second strongest in the obturator region, and weakest in the external iliac region. These results indicate that the major lymphatic channels involved in the spread of bladder cancer are those along the inferior vesical artery to the internal iliac artery.…”
Section: Discussionmentioning
confidence: 58%
“…7 We previously found that use of a fluorescence navigation (FN) system with ICG injection was safe and convenient in determining the border between normal and malignant kidney tissues during partial nephrectomy 8 and in identifying lymphatic vessels draining from the prostate; these findings validated the concept of SLNs in prostate cancer. 9 However, to the best of our knowledge, there are no reports on the use of ICG fluorescence navigation for SLN mapping in bladder cancer patients. …”
Section: Introductionmentioning
confidence: 99%
“…In its current form however, SLNB lacks not only the support of large, multi-centre studies but, like its predecessors in penile and pelvic malignancy, continues to be plagued by concerns around high false negative rates. With the investigation to T1 weighted MR, identifying all six cervical nodes, compared to just four [48] . The first use of NIRF in urogenital malignancy was in 2011, when lymphatic pathways in prostate cancer were mapped with indocyanine [49] .…”
Section: Resultsmentioning
confidence: 99%
“…Les ganglions inguinaux ont été considérés comme bénins, ne correspondant pas au territoire de drainage du cancer de prostate [14,15]. Pour les patients avec preuve histologique prostatique (biopsie ou exérèse chirurgicale), la concordance avec les images TEP a été évaluée en comparaison avec le compte rendu histologique détaillé.…”
Section: Gold Standard Et Analyse Statistiqueunclassified